SUBSTANTIVE CHARACTERISTICS OF PROFESSIONAL IMAGE: BEFORE STATING THE PROBLEM (Pedagogy of Higher and Secondary Education, 2022)
It is main to collect the professional prepearing of future tcachers imidgining as a part of methodological culture
Keywords: 0